2016
DOI: 10.1007/978-3-319-30569-1_16
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Cores: The Terminus of an Intelligent Viral Meme’s Trajectory

Abstract: Comprehending the virality of a meme can help scientists address problems pertaining to disciplines like epidemiology and digital marketing. Therefore, it does not come as a surprise that meme virality stands out as an integral component of research in complex networks, today. In this paper, we explore the possibility of artificially inducing virality in a meme by intelligently directing a meme's trajectory in the network. Keeping in mind the importance of core nodes in a core-periphery structure, we propose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Table 1 shows that the core constitutes less than 2 percent of the whole network. Gupta et al [47] observed that few innermost shells close to nucleus have the same influential power as core and have very high density. In practical use, a very small percentage of nodes from innermost layers can also be considered as core nodes.…”
Section: Evolution Of Core Structurementioning
confidence: 99%
“…Table 1 shows that the core constitutes less than 2 percent of the whole network. Gupta et al [47] observed that few innermost shells close to nucleus have the same influential power as core and have very high density. In practical use, a very small percentage of nodes from innermost layers can also be considered as core nodes.…”
Section: Evolution Of Core Structurementioning
confidence: 99%
“…al. has referred such nodes as "Pseudocores" [46] in their work. Our experiments demonstrate the disappearance of pseudo-cores when the edge weights are considered in the diffusion process.…”
Section: Experimental Verificationmentioning
confidence: 99%
“…In Layer 1 (L 1 ) and Layer 2 (L 2 ), the list of core nodes is [9,2,7,3,5,4,11,15,16,13] and [3,5,6,9,11,4,7,8] respectively. The common set of nodes S between L 1 and L 2 is [3,4,5,7,9,11], and union between the two lists is [2,3,4,5,6,7,8,9,11,13,15,16]. The Coreness SimðL 1 ; L 2 Þ ¼ 0:5 by using Eq.…”
Section: Illustration With a 2-layered Networkmentioning
confidence: 99%
“…As the study on monoplex network [4] reported existence of core-periphery structure [6] in real world network, the core of such networks plays an important role in maximizing the diffusion in the network [7]. In multiplex network, each layer has its own core-periphery structure.…”
Section: Introductionmentioning
confidence: 97%